Perfusate Metabolomics Content and Expression of Tubular Transporters During Human Kidney Graft Preservation by Hypothermic Machine Perfusion. Issue 9 (20th April 2022) - Faucher, Quentin; Alarcan, Hugo; Sauvage, François-Ludovic; Forestier, Lionel; Miquelestorena-Standley, Elodie; Nadal-Desbarats, Lydie; Arnion, Hélène; Venhard, Jean-Christophe; Brichart, Nicolas; Bruyère, Franck; Marquet, Pierre; Barin-Le Guellec, Chantal
Abstract : Background: Ischemia-related injury during the preimplantation period impacts kidney graft outcome. Evaluating these lesions by a noninvasive approach before transplantation could help us to understand graft injury mechanisms and identify potential biomarkers predictive of graft outcomes. This study aims to determine the metabolomic content of graft perfusion fluids and its dependence on preservation time and to explore whether tubular transporters are possibly involved in metabolomics variations. Methods: Kidneys were stored on hypothermic perfusion machines. We evaluated the metabolomic profiles of perfusion fluids (n = 35) using liquid chromatography coupled with tandem mass spectrometry and studied the transcriptional expression of tubular transporters on preimplantation biopsies (n = 26), both collected at the end of graft perfusion. We used univariate and multivariate analyses to assess the impact of perfusion time on these parameters and their relationship with graft outcome. Results: Seventy-two metabolites were found in preservation fluids at the end of perfusion, of which 40% were already present in the native conservation solution. We observed an increase of 23 metabolites with a longer perfusion time and a decrease of 8. The predictive model for time-dependent variation of metabolomics content showed good performance (R 2  = 76%, Q 2  = 54%, accuracy = 41%, and permutation test significant). Perfusion time did not affect the mRNA expression of transporters. We found no correlation between metabolomics and transporters expression. Neither the metabolomics content nor transporter expression was predictive of graft outcome. Conclusions: Our results call for further studies, focusing on both intra- and extratissue metabolome, to investigate whether transporter alterations can explain the variations observed in the preimplantation period.